1996
DOI: 10.1177/1045389x9600700210
|View full text |Cite
|
Sign up to set email alerts
|

Vibration Control for Precision Manufacturing Using Piezoelectric Actuators

Abstract: ABSTRACTreasonable stroke limits, all of which can be used to increase performance levels in precision manufacturing systems. This paper describes two examples of embedding piezoelectric actuators in structural components for vibration control. One example involves suppressing the self excited chatter phenomenon in the metal cutting process of a milling machine and the other involves damping vibrations induced by rigid body stepping of a photolithography platen. Finite element modeling and analyses are essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Martinez et al [59] demonstrated the feasibility of piezoelectric stack actuators in chatter reduction. Their experimental setup employed a surrogate machine tool structure composed of a positive position feedback (PPF) filter and a cantilever solid bar.…”
Section: Active and Passive Vibration Controlmentioning
confidence: 99%
“…Martinez et al [59] demonstrated the feasibility of piezoelectric stack actuators in chatter reduction. Their experimental setup employed a surrogate machine tool structure composed of a positive position feedback (PPF) filter and a cantilever solid bar.…”
Section: Active and Passive Vibration Controlmentioning
confidence: 99%
“…Fortunately, because of their large forcing capabilities, it is possible to employ various amplification techniques that sacrifice some of this forcing potential to amplify the actuator's stroke. Several researchers have been successful in employing external leveraging mechanisms coupled with piezoelectric stacks to amplify actuator displacement 1,2,3 for a variety of applications such as heavy machinery isolation mounts 4,5 , active rotor blade flaps 6,7,8 , and fuel injectors 9 . While these externally amplified actuators posses a high power efficiency for a given actuator mass, the additional components necessary for this amplification greatly reduce the actuator's volumetric power efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include the Moonie 20 , Cymbal 21 , X-frame 22 and double X-frame 23 . These actuators are employed primarily in high force applications such as proof mass actuation 24 , micropositioning 25,26 , and active/passive vibration control 27 , particularly in helicopter rotor blades [28][29][30][31][32][33][34][35] , suspension control 36 and vibration damping in machine tools 37 .…”
Section: Introductionmentioning
confidence: 99%